Derived appendicular morphology in Early Cretaceous aquatic turtles evidenced by the track record. (17th July 2013) - Hornung, Jahn J.; Reich, Mike
<x xml:space="preserve">Abstract</x> A well‐preserved isolated manus impression evidences the presence of derived aquatic adaptations in the forelimb morphology of Berriasian turtles. Size and the abundant co‐occurring turtle fauna indicate that the track was left by a large‐sized, bottom‐walking basal pancryptodiran. The footprint shows an interesting mosaic of primitive and derived features. The basic turtle pattern is reflected by a short and broad autopodium but thin phalanges, claw reduction and extensive webbing enclosing the digits and lateral and medial margins of the distal metapodium are clearly specialized features related to the aquatic environment. Some characters including the proportional elongation of the first digit, which reached as far distally as the other digits and was probably highly mobile at the metacarpal‐phalangeal joint, indicate an even higher degree of specialization. The specimen gives evidence on a hitherto unknown range of appendicular modification in Early Cretaceous turtles, and redundantly proves the aquatic habitat and locomotion of large‐sized turtles from the Berriasian of northwestern Germany.